Environmental and dam effects on cannibalism in Wistar rat litters - Graziela Tarôco; Leila de Genova Gaya; Daniela Regina Resende; Ivan Carlos dos Santos; Ana Paula Madureira (Acta Scientiarum. Biological Sciences, 2015)
The factors related to cannibalistic behavior of dams in a Wistar rat colony are identified and analyzed. The maternal genetic effects were tested as a random effect by the method of generalized linear models. The season at parturition, the dam´s age at parturition and the density of the room at parturition were tested as fixed effects, whereas the litter size at birth was tested as a co-variable. The genetic effect of the dam was significant for the number of cannibalized pups. Although the season at parturition, the dam´s age and room density on the day of parturition were not individually significant (p > 0.05), most of the interactions between the variation sources were significant (p < 0.05). Cannibalism occurred mostly in dams aged over 241 days, with parturition during spring. So that occurrences of cannibalism could be avoided, dams with the smallest number of cannibalized pups should be selected, coupled to dams younger than 241 days, breeding during spring. The above strategies may reduce the number of couples in the vivarium and increase their production efficiency.